Social Assistance and Birth Outcomes: Evidence from the Uruguayan PANES - Veronica Amarante; Marco Manacorda; Edward Miguel; Andrea Vigorito (Inter-American Development Bank (IDB), 2011)
This paper estimates the impact of a large temporary poverty relief program, Uruguays PANESon birth outcomes. Using program administrative data and longitudinal vital statistics, a significant and precisely estimated reduction in the fraction of low-weight newborns (less than 2,500 g. ) on the order of 10 to 20 percent was found to be a result of treatment. The cash (and in-kind) transfer components of the program were considered to drive the results, suggesting that unrestricted social assistance has the potential to positively affect birth outcomes, most likely through improved nutrition. Assuming that all the effect of the program was through the transfer, an elasticity of low birthweight with respect to welfare transfers on the order of around 0. 30 can be inferred.
Keywords: I18; I32; I38; J13; 330